Social snacking with a virtual agent – On the interrelation of need to belong and effects of social responsiveness when interacting with artificial entities. Issue 109 (January 2018) - Krämer, Nicole C.; Lucas, Gale; Schmitt, Lea; Gratch, Jonathan
Highlights: A socially responsive virtual agent can provide "social snacking", i.e. diminish the need for social contact. The agent´s socially responsive behavior is especially influential when users´ need to belong is high. Social effects of a virtual agent are dependent on the users´ personality. Abstract: Based on considerations that people´s need to belong can be temporarily satisfied by "social snacking" (Gardner et al., 2005) in the sense that in absence of social interactions which adequately satisfy belongingness needs surrogates can bridge lonely times, it was tested whether the interaction with a virtual agent can serve to ease the need for social contact. In a between subjects experimental setting, 79 participants interacted with a virtual agent who either displayed socially responsive nonverbal behavior or not. Results demonstrate that although there was no main effect of socially responsive behavior on participants´ subjective experience of rapport and on connectedness with the agent, those people with a high need to belong reported less willingness to engage in social activities after the interaction with a virtual agent – but only if the agent displayed socially responsive behavior.